Observation of iron diffusion in the near-surface region of magnetite at 470 K - Steffen Tober; Marcus Creutzburg; Björn Arndt; Konstantin Krausert; Stefan Mattauch; Alexandros Koutsioubas; Sabine Pütter; Amir Syed Mohd; Lukas Volgger; Herbert Hutter; Heshmat Noei; Vedran Vonk; et al. (Physical Review Research, 2020)
Experiments are reported, which allow us to quantify the near-surface cation diffusion in (001) oriented Fe_{3}O_{4} single crystals at temperatures between 470 and 770 K. Thin homoepitaxial films of magnetite, grown using isotopically labeled ^{57}Fe, were investigated by neutron reflectivity and time-of-flight secondary ion mass spectrometry. By heating the thin films in high vacuum to different temperatures for a well-defined time and determining the ^{57}Fe distribution along the surface normal, the diffusion lengths are obtained. For the investigated temperature range, diffusion constants of the order of 10^{−20} m^{2}/s are deduced. These results are important in view of near-surface mass transport induced by oxygen chemical potential differences occurring when magnetite is exposed to different gas atmospheres or by adsorbates.